Tie the straps: Uniform bootstrap con fidence bands for bounded influence curve estimators - Wolfgang Karl Härdle; Ya'acov Ritov; Weining Wang (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2013)
We consider theoretical bootstrap coupling techniques for nonparametric robust smoothers and quantile regression, and verify the bootstrap improvement. To cope with curse of dimensionality, a variant of coupling bootstrap techniques are developed for additive models with both symmetric error distributions and further extension to the quantile regression framework. Our bootstrap method can be used in many situations like constructing con dence intervals and bands. We demonstrate the bootstrap improvement over the asymptotic band theoretically, and also in simulations and in applications to firm expenditures and the interaction of economic sectors and the stock market.
Keywords: C00; C14; 330; Nonparametric Regression; Bootstrap; Quantile Regression; Confi dence Bands; Additive Model; Robust Statistics